Financial Cycles in Euro Area Economies: A Cross-Country Perspective Using Wavelet Analysis - Martin Mandler; Michael Scharnagl (Oxford Bulletin of Economics and Statistics, 2021)
We study the cross-country dimension of financial cycles for six euro area countries using wavelet analysis. Estimated wavelet cohesions show that cycles in equity prices and interest rates display stronger synchronization across countries than real output cycles, whereas credit variables and house prices show lower cross-country synchronization. We propose a wavelet-based extension to the spectral envelope that is similar to a frequency-based time-varying principal component analysis. The country loadings show that, contrary to all other variables, cycles in loans to households and house prices in Germany and the Netherlands are negatively or less strongly correlated with the common cycles.
Keywords: 330